An update on miRNAs as biological and clinical determinants in colorectal cancer: a bench-to-bedside approach. (June 2015) - Weng, Wenhao; Feng, Junlan; Qin, Huanlong; Ma, Yanlei; Goel, Ajay
ABSTRACT : Colorectal carcinogenesis represents a sequential progression of normal colonic mucosa from adenoma to carcinoma. It has become apparent that miRNA deregulation contributes to the initiation and progression of colorectal cancer (CRC). These oncogenic or tumor-suppressive miRNAs interact with intracellular signaling networks and lead to alteration of cell proliferation, apoptosis, metastasis and even response to chemotherapeutic treatments. This article aims to review the cutting edge progress in the discovery of the role of novel mechanisms for miRNAs in the development of CRC. We will also discuss the potential use of miRNAs as biomarkers for early diagnosis and prognosis of CRC. Furthermore, with advancements in RNA delivery technology, it is anticipated that manipulation of miRNAs may offer an alternative therapy for CRC treatment.